Sunnis and Shiites in Iraq: From Hate Language to Reconciliation – A Framework for Reconciliation Based on the Works of Sayyed Mohammad Hussein Fadlallah and Shaikh Mohmood Shaltoot on De-escalating Sectarian Tension - Jafer, Waged (Université Saint-Paul / Saint Paul University, 2012)
For almost 14 centuries, religious bigotry led to violence and conflict between the Sunnis and the Shiites around the world, creating sectarian tension between them regardless of the immense commonality that they share within their belief systems. The division between them created a rift of mutual stereotypes and isolation as time went by. This reality of schismatic conflict raises the question of whether or not Islam holds the key to transforming the conflict so that positive relationships can be established. As a minor step towards reconciliation, a framework for reconciliation among the two sects will be presented by focusing at the work of two scholars that played a major role in de-escalating the conflict between Sunnis and Shiites; as they have both worked on a common principle of reconciliation and coexistence. The Shiite scholar intended for this study is Sayyed Mohammad Hussein Fadhlallah and the Sunni scholar is Sheikh Mahmood Shaltoot. Hence, the aim of this study is to follow the trail they left behind, hoping to implement their ideology of peace and reconciliation in a modified, effective framework that could generate a change in attitude and perceptions. The idea is to provide an effective reconciliation proposal that seeks common goals and interests in unity and coexistence between the two sects. This framework has its roots in the thoughts and teachings of Fadhlallah and Shaltoot and is developed by theories in Conflict Resolution. The framework was eventually analysed using the expertise and knowledge of some of the prominent religious leaders from Iraq and Lebanon in order to finalize and conclude the applicability of the framework as a conflict resolution strategy on de-escalation of sectarian violence; aiming for coexistence.